Natural Pentacyclic Triterpenoid as Allosteric Modulators of Human 5-Lipoxygenase with Potential Anti-Inflammatory Activity - Torres-Gaona, M; Garcia Huidobro-Toro, J; Mascayano-Collado, C; Muñoz-Osses, M; Muñoz-Osses, M; Navarrete-Tudela, E (Taylor and Francis Ltd., 2024)
This study explored new methods to inhibit human 5-lipoxygenase (5-hLOX) by analyzing natural terpenes that share structural similarities with acetoxyboswellic acid (AKBA). Enzymatic assays were used to evaluate the terpene’s ability to inhibit the enzyme, potentially providing anti-inflammatory benefits. Our research focused on how certain types of triterpenes can inhibit 5-hLOX allosterically via a newly discovered allosteric site identified by enzyme crystallization. To determine whether natural boswellic acid analogs mimicked the allosteric known inhibitor AKBA, we combined 5-hLOX inhibition with in silico modeling. Our research has discovered that certain amino acids, specifically Arg 138, Arg 101, Arg 68, and Gln129, located in the allosteric 5-hLOX pocket, play a critical role in stabilizing glycyrrhetinic isomers. These amino acids form hydrogen bonds and hydrophobic interactions that contribute to the inhibitory potency of boswellic acid derivatives. We have found that α and β glycyrrhetinic acid isomers, carbenoxolone, and to a minor extent, prednisolone, have a potent inhibitory effect against 5-hLOX with IC50 values of 8.64, 3.94, 52.98, and 291.20 µM, respectively. These values are in line with our calculated in silico allosteric site binding energy estimations. In contrast, other steroidal or non-steroidal anti-inflammatory agents exhibited inhibitory potencies larger than 500 μM. However, the specific pharmacodynamic mechanisms are currently unknown. We propose that AKBA analogs may lead to the future development of novel anti-inflammatory agents. Communicated by Ramaswamy H. Sarma. © 2023 Informa UK Limited, trading as Taylor & Francis Group.